2008
DOI: 10.1001/jama.299.11.1277
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Analysis of Association Between <emph type="ital">LRP5</emph> and <emph type="ital">LRP6</emph> Variants and Osteoporosis

Abstract: Drs Ioannidis and Trikalinos had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis. Drs van Meurs and Trikalinos contributed equally to this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
3
10

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(181 citation statements)
references
References 68 publications
8
158
3
10
Order By: Relevance
“…The Wnt signaling pathway is the key regulator of bone mass. The Wnt co-receptor lipoprotein receptor-related proteins, LRP5 (6)(7)(8)10,11) and LRP6, (19,20) were associated with BMD at the GWAS level, whereas WNT4, a member of the Wnt ligands, was associated with vertebral CSA in older Caucasian men. (22) TNFRSF11A was significantly associated with osteoporotic fracture in the collaborative meta-analysis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The Wnt signaling pathway is the key regulator of bone mass. The Wnt co-receptor lipoprotein receptor-related proteins, LRP5 (6)(7)(8)10,11) and LRP6, (19,20) were associated with BMD at the GWAS level, whereas WNT4, a member of the Wnt ligands, was associated with vertebral CSA in older Caucasian men. (22) TNFRSF11A was significantly associated with osteoporotic fracture in the collaborative meta-analysis.…”
Section: Discussionmentioning
confidence: 95%
“…The criteria for exclusion was a history of: (1) serious residual effects of cerebral vascular disease; (2) diabetes mellitus, except for adult asymptomatic hyperglycemia controlled by diet; (3) chronic renal disease manifested by a serum creatinine level of 11.9 mg/dL; (4) chronic liver disease or alcoholism; (5) chronic lung disease; (6) 12 weeks of corticosteroid therapy at pharmacologic levels; (7) 6 months of treatment with anticonvulsant therapy; (8) evidence of other metabolic or inherited bone diseases (eg, hyperparathyroidism or hypoparathyroidism, Paget's disease of bone, osteomalacia, or osteogenesis imperfecta); (9) rheumatoid arthritis or collagen disease; (10) major gastrointestinal disease (eg, peptic ulcer, malabsorption, chronic ulcerative colitis, regional enteritis, or any significant chronic diarrhea); (11) significant disease of any endocrine organ that would affect bone mass (eg, Cushing's syndrome or hyperthyroidism); (12) any neurologic or musculoskeletal condition that would be a nongenetic cause of low bone mass; (13) any disease, treatment, or condition that would be a nongenetic cause of low bone mass; or (14) any previous bisphosphonate treatment or current use of hormone replacement therapy.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Wnt pathway genes have been associated with BMD phenotypes, ranging from osteoporosis (Butler et al 2011) to the high bone mass (HBM) (Boyden et al 2002). Among these, LRP5 is recognized as one of the key bone regulatory genes that might influence BMD in the general population, and LRP5 polymorphisms have been consistently associated with BMD in different populations (Richards et al 2008;van Meurs et al 2008;Rivadeneira et al 2009). More recently WNT3A, known to affect osteoblast differentiation (Monroe et al 2012), was found to be associated with BMD in Australian postmenopausal women (Sims et al 2008); a meta-analysis combining five GWAS identified a large linkage disequilibrium (LD) block encompassing LRP4 associated with femoral neck and lumbar spine BMD (Styrkarsdottir et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…More recently WNT3A, known to affect osteoblast differentiation (Monroe et al 2012), was found to be associated with BMD in Australian postmenopausal women (Sims et al 2008); a meta-analysis combining five GWAS identified a large linkage disequilibrium (LD) block encompassing LRP4 associated with femoral neck and lumbar spine BMD (Styrkarsdottir et al 2008). It has also been suggested that LRP6 polymorphisms influence BMD (Sims et al 2008;van Meurs et al 2008); however, the results have been conflicting (Mencej-Bedrac et al 2009;Yerges et al 2010). Recently, Estrada et al (2012) performed a metaanalysis including data from 17 genome-wide association studies of European and East Asian ancestry, highlighting the critical role of several genes (WNT16, LRP5, DKK1, LRP4, WNT4.…”
Section: Introductionmentioning
confidence: 99%